Perioperative Complications after Kasai Hepatoportoenterostomy: Data from the Swiss National Biliary Atresia Registry - Calinescu, Ana M.; Wilde, Jim C. H.; Korff, Simona; McLin, Valérie A.; Wildhaber, Barbara E. (European Journal of Pediatric Surgery, 2020)
Introduction Hepatoportoenterostomy (HPE) is the first-line treatment for biliary atresia (BA) patients. This study aims to describe perioperative complications after HPE and to analyze their impact on outcome.Materials and Methods Patients with HPE (Swiss National Biliary Atresia Registry, 1994–2017) were retrospectively analyzed. Perioperative complications were defined as complications occurring up to 30 days after surgery. Surgical complications were defined as directly related to the surgical act; medical complications were defined as any other deviation from the uneventful postoperative course.Results Sixty-two patients were included. Median age at HPE was 63 days (18–126). Twenty six patients out of 62 (42%) had ≥ 1 complications: 6/62 (10%) surgical, 24/62 (39%) medical, that is, we observed 7 surgical and 28 medical complications. As for medical complications, cholangitis was the most frequent: 19/28 (68%). Lower gestational age at birth correlated with more overall complications (p = 0.02). Age, weight at HPE, syndromic BA, and postoperative steroid administration were not significantly correlated. There were no perioperative deaths. Perioperative complications did not correlate with overall survival (p = 0.14) and survival with native liver (p = 0.55).Conclusion HPE is often associated with perioperative medical complications. Lower gestational age at birth was significantly associated with more complications. Perioperative complications had no impact on overall outcome.
Keywords: hepatoportoenterostomy; biliary atresia; complications